ROH KUDUS DALAM MARIOLOGI MASA KINI : Keluar dari Medan Implisit - Arnold Suhardi (Litbang STFT Widya Sasana Malang, 2005)
In traditional Mariology theologians tend to reflect and present the real intervention of Mary in her relationship with the Church. The problem of this approach is that Mary is not put in her clear and explicit relationship with the Holy Trinity, Christ and the Holy Spirit that enable her to play an unique role in the history of salvation. Consequently, in popular devotion one can find expressions that do not reveal the real place and role of Mary based on the biblical inspiration. Now, in post-conciliar theology there is an urgent need not only to reflect and presentate Mary in her relationship with another mysteries of faith, and especialy in this context, with the Holy Spirit, but also to reformulate the devotional expressions in accordance with theological sensitivities of our day.